(untitled) (Annals of Medical Research, 2021)
Aim: Iron overload in tissues, despite current chelation therapies, is a major cause of organ dysfunction and serious complications in thalassemia major. Similarly, iron accumulation in endocrine tissues pave the way for various endocrinopathies. Previous reports regarding prevalence of endocrinopathies in thalassemia major varies significantly based on study population. In this study, we aimed to investigate the metabolic and endocrine disorders among the transfusion-dependent adult thalassemia major patients.Materials and Methods: Data from transfusion-dependent adult thalassemia major patients with regular follow-up were retrospectively evaluated. Former records of the patients were examined to evaluate endocrine disorders, on the basis of laboratory test results. Results: A total of 76 patients with a median age of 28 years, composed of 39 (51.3%) female and 37 (48.7%) male patients were included. Out of the entire cohort, 36.8% (n=28) had hypogonadism, 30.3% (n=23) had thyroid dysfunction, 28.9% (n=22) had a glucose metabolism disorder and 7.9% (n=6) had hypoparathyroidism. Hypogonadism was encountered in 38.5% (n=15) of females and in 35.1% (n=13) of males. Only one patient from each gender had hypergonadotropic hypogonadism, possibly related to iron overload, while the rest had hypogonadotropic hypogonadism. A positive history of delayed puberty was noted in 30.8% (n=12) of females and 24.3% (n=9) of males. Of the patients, 30.3% (n=23) had one, 18.4% (n=14) had 2, 10.5% (n=8) had 3, and 1.3% (n=1) had 4 different endocrine dysfunctions. Accordingly, 61.5% of the patients had at least one endocrine dysfunction while only 39.5% (n=30) had no endocrine dysfunction at all. Conclusion: Survival time has been prolonged in patients with thalassemia major by virtue of effective transfusion and chelation therapies. As a consequence of prolonged survival, endocrine dysfunctions commonly strike adult thalassemia major patients, therefore, endocrine functions need to be evaluated at regular intervals during follow-up.